Enhancing strategic planning in the UAE public sector: the impact of business intelligence and technological capabilities - Alketbi, Hamad Mohamed Faris Ali (2024)
The main objective of this study is to investigate the impact of business intelligence and technological competencies on strategic planning in the UAE public sector. The problem of the study was represented in the problems and obstacles faced by the UAE public sector within the framework of the process of benefiting from modern tools such as business intelligence, specifically business reports and inquiries, business perspectives, business performance management, and the development of technological competencies. This specifically focuses on the acquisition of technology and analytical skills, so that this sector becomes able to play the role that is required for the success of the strategic planning process in the UAE public sector institutions. The study adopted quantitative approach and made use of statistical evaluation based on detailed solutions and techniques of variance, covariance, correlation and regression. A questionnaire was created from previous literary works and modified to match the study conditions. The study population comes from the employees of the various departments working in the UAE public sector, and this consists, according to the Federal Center for Competitiveness and Statistics, around (1500) employees. The target sample size is 306, but the valid data set for analysis was 329 questionnaires. The model can explain 70% of the change in the dependent variable, which is strategic management planning (SMP) in public sector institutions, which reflects a clear impact size that answers the research questions about the extent of the impact of business intelligence (BI) and technological competencies (TC) through their different dimensions, namely, Business Reports and Inquiries (BRQ), Business Perspectives (BV), Business Performance Management (BPM), Technology Acquisition (TA), and Analytical Skills (AS) on Strategic Management Planning (SMP) in UAE public sector organizations. The study recommended conducting similar studies in other places such as other emirates or neighbouring countries. The study also recommended conducting similar studies using different methodology such as qualitative approach, which may infer additional variables that may not have been included in the current research.